2018
DOI: 10.1111/den.13012
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian network meta‐analysis: Efficacy of air insufflation, CO2 insufflation, water exchange, and water immersion in colonoscopy

Abstract: Air insufflation might be the most unsatisfactory colonoscopy. Meanwhile, water exchange might be the most efficient colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…Evidence supports that WE colonoscopy is the least painful insertion technique and decreases the need for sedation, significantly increasing colon cleanliness and lesion detection, for example, the adenoma detection rate (ADR), a key colonoscopy performance indicator. [2][3][4][5][6][7][8] However, compared with air or carbon dioxide insufflation (GAS), WE usually requires a longer insertion time. [2][3][4][5][6][7] This has a negative impact on room turnaround efficiency and contributed to hampering its wider adoption in clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supports that WE colonoscopy is the least painful insertion technique and decreases the need for sedation, significantly increasing colon cleanliness and lesion detection, for example, the adenoma detection rate (ADR), a key colonoscopy performance indicator. [2][3][4][5][6][7][8] However, compared with air or carbon dioxide insufflation (GAS), WE usually requires a longer insertion time. [2][3][4][5][6][7] This has a negative impact on room turnaround efficiency and contributed to hampering its wider adoption in clinical practice.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] However, compared with air or carbon dioxide insufflation (GAS), WE usually requires a longer insertion time. [2][3][4][5][6][7] This has a negative impact on room turnaround efficiency and contributed to hampering its wider adoption in clinical practice. [9][10][11] A meta-analysis 7 reported that despite the longest cecal intubation time with WE, it is still comparable with other insertion methods.…”
mentioning
confidence: 99%
“…Actually, previous reports concluded that CO 2 I was associated with the equivalent ADR compared with AI [20,28,29]. It was reported that CO 2 I was associated with the equivalent ADR compared with AI from 16 randomized controlled trials, of which indications of colonoscopy were mainly screening [29]. Although there is a report suggesting CO 2 I was significantly associated with the higher ADR than AI, in this retrospective study, only expert performed colonoscopy and patients undergoing a screening colonoscopy, a surveillance colonoscopy after a post-endoscopic resection of colorectal neoplasms or a colonoscopy for the investigation of positive results of a fecal occult blood test screening, per rectum bleeding, iron deficiency anemia or abdominal pain were eligible for enrollment [27].…”
Section: Discussionmentioning
confidence: 98%
“…Although previous studies showed that CO 2 I was associated with a decrease in abdominal pain [19], the data regarding how CO 2 I is associated with the ADR are limited. Actually, previous reports concluded that CO 2 I was associated with the equivalent ADR compared with AI [20,28,29]. It was reported that CO 2 I was associated with the equivalent ADR compared with AI from 16 randomized controlled trials, of which indications of colonoscopy were mainly screening [29].…”
Section: Discussionmentioning
confidence: 99%
“…Spätestens bei Auftreten einer Perforation wurde auf CO 2 -Insufflation umgestellt, wie es empfohlen wird [1,33]. Mittlerweile verwenden wirden aktuellen Leitlinien folgendbei nahezu allen Endoskopien grundsätzlich CO 2 als Standard [69][70][71].…”
Section: Introductionunclassified